Getting added value out of accruals reforms - Moretti, Delphine (OECD Publishing, 2018)
After three decades of public financial management reforms, around three quarters of OECD countries are using accrual accounting with some adopting accrual budgeting as well (OECD Accruals 2016 Survey). This is however a sensitive time: questions are increasingly being raised on the cost and usefulness of accrual reforms, whose impacts on public management and performance are not obvious to many stakeholders. Against this background, this study brings together the experience of eleven countries that have introduced accrual accounting and/or accrual budgeting into their public sector. It aims at summarizing initial objectives of accrual reforms, countries' own assessment of how well these objectives have been achieved and propose recommendations on how finance ministries should go about achieving maximum outcomes from their transition to accrual accounting. JEL code : H50, H60, H83 Keywords : accrual accounting, accrual reform, budgeting, transparency, performance
Keywords: Finance and Investment; Governance; Economics